Teflon Granuloma in the Nasopharynx: A Potentially False-Positive PET/CT Finding - Harrigal, Chivonne (AJNR Am J Neuroradiol, 2005)
Summary: Positron emission tomography (PET) has become a critical diagnostic tool in the discovery and staging of malignancies in the head and neck. Although PET is accurate for detecting cancer, increased 18 F-fluorodeoxyglucose (FDG) uptake can be seen in healthy tissues such as muscle, fat, and glands and uptake can be seen in tissues affected by inflammation or granulomatous disease. Combined PET and CT (PET/CT) can often overcome these difficulties by fusing anatomic and physiological data, but radiographic findings of some disease processes can be confusing even with fused imaging techniques. We present two cases of FDG uptake in the posterior pharynx, localized by combined PET/CT, which was initially interpreted as squamous cell carcinoma. The increased activity was ultimately attributed to Teflon-induced granulomas. It is important for radiologists to recognize potential causes of false-positive PET/CT findings to improve our diagnostic accuracy and to avoid unnecessary biopsies and surgeries.